Analisis Kepatuhan Petugas Dalam Pengentrian Pelaporan Pada Website SIGIZIKESGA Di Kabupaten Musi Rawas Utara - Istila’a Khairotun Nisa; Gema Asiani; Arie Wahyudi (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
The SIGIZIKESGA website is an information system that supports the management of nutrition and maternal-child health data as a basis for health program planning. Compliance of health workers in reporting data entry is essential to ensure accurate and timely data. Objective of this study to analyze the compliance of health workers in reporting data entry on the SIGIZIKESGA website in North Musi Rawas Regency in 2026. This study employed an analytical cross-sectional design involving 64 health workers selected through total sampling. Data were collected using questionnaires and analyzed using the Chi-Square test and multiple logistic regression. The findings showed that knowledge (p=0.000; OR=7.70), attitude (p=0.040; OR=4.11), supervisor support (p=0.020; OR=5.47), and workload (p=0.000; OR=11.88) were significantly associated with workers' compliance. Meanwhile, age, education level, length of service, training, and facilities and infrastructure were not significantly associated with compliance. Multivariate analysis revealed that knowledge was the most dominant factor influencing compliance, with a probability of 20%. Improving health workers' knowledge plays a crucial role in enhancing compliance with reporting data entry on the SIGIZIKESGA website.